2019
DOI: 10.1177/1479973119867954
|View full text |Cite
|
Sign up to set email alerts
|

Treatable traits in acute exacerbations of chronic airway diseases

Abstract: Acute exacerbations of chronic airway disease are common occurrences that cause a major burden of illness. Acute exacerbations are associated with impaired health status, increased lung function decline, hospitalization and increased risk of death. Exacerbation avoidance is a major priority. Despite this goal, exacerbations continue to occur and the need for effective models of care that optimize patient outcomes are urgently needed. ‘Treatable Traits’ is an approach to personalized medicine that has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 119 publications
(130 reference statements)
1
53
0
1
Order By: Relevance
“…Sarcopenia has, however, been highlighted as an important 'treatable trait' in adult respiratory medicine. 59 One of the few studies to explore this area was conducted by Jones et al 2 who demonstrated that pulmonary rehabilitation, a comprehensive, multicomponent exercise-based intervention, improved a range of clinical outcomes and reduced the incidence of sarcopenia in a cohort of patients with COPD. More research is clearly warranted to further validate the findings of Jones and colleagues, including the use of other recommended adjunctive therapies such as nutritional supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia has, however, been highlighted as an important 'treatable trait' in adult respiratory medicine. 59 One of the few studies to explore this area was conducted by Jones et al 2 who demonstrated that pulmonary rehabilitation, a comprehensive, multicomponent exercise-based intervention, improved a range of clinical outcomes and reduced the incidence of sarcopenia in a cohort of patients with COPD. More research is clearly warranted to further validate the findings of Jones and colleagues, including the use of other recommended adjunctive therapies such as nutritional supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review has highlighted the clinical relevance of including measurements of muscle mass, muscle strength, and physical performance in individuals with COPD, as these variables clearly associate with sarcopenia, exacerbations, and poor prognosis. 47,59 The more widespread implementation of these measures in clinical practice could help identify patients with COPD at increased risk of future healthcare use related to exacerbations. 47,65 This is also an important priority from a public health economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…One study of sputum NE activity in a large population of adults with bronchiectasis found an association of increased activity and future risk of exacerbation, offering the promise of an easily-obtainable bio-marker for clinical surveillance (24,114). There is robust research presently underway to identify clinical phenotypes and so-called "treatable traits" in non-CF bronchiectasis, which will one day permit more precise and tailored management strategies (115,116).…”
Section: Future Directions In Bronchiectasis Managementmentioning
confidence: 99%
“…The COVID-19 telehealth rehabilitation programme consisted of (1) a comprehensive initial rehabilitation assessment with a physiotherapist for identification of symptoms and physical impairments that were considered treatable (i.e. treatable traits) [7] within the PR context [8];…”
Section: Case Seriesmentioning
confidence: 99%